Predictive role of heterozygous p.R4810K of RNF213 in the phenotype of Chinese moyamoya disease. (18th February 2020) - Wang, Yue; Zhang, Zhengshan; Wei, Ling; Zhang, Qian; Zou, Zhengxing; Yang, Luping; Li, Desheng; Shang, Mengke; Han, Cong; Mambiya, Michael; Bao, Xiangyang; Li, Qian; et al.
Abstract : Objective: Precise genetic analyses were conducted with ring finger protein 213 ( RNF213 ) in relation to a particular clinical phenotype in Chinese patients with moyamoya disease (MMD) to determine whether heterozygosity is responsible for the early-onset and severe form of this disease. Methods: A case–control study for RNF213 p.R4810K involving 1, 385 Chinese patients with MMD and 2, 903 normal control participants was performed. Correlation analyses between genotype and phenotype or different clinical features were also statistically explored. Results: An obvious trend was observed: the carrying rate of RNF213 p.R4810K gradually decreased when moving from coastal cities in northeast, north, and east China to southern cities or inland areas. Higher frequencies of p.R4810K were observed in patients with MMD compared with control participants (odds ratio, 48.1; 95% confidence interval, 29.1–79.6; p = 1.6 × 10 −141 ). In addition, the onset age of all patients with the GA and AA genotypes were lower than with the GG genotype, and the median onset age was 40.0, 36.0, and 11.5 years with GG, GA, and AA, respectively, thereby confirming that those with GA or AA could acquire MMD during early life stages. Patients with MMD with the GA genotype were more susceptible to posterior cerebral artery (PCA) involvement compared to those with the GG genotype (38.4% vs 23.3%, p = 8.3 × 10 −7 ). Conclusions: Strong evidence suggests that the carrying rate of RNF213 p.R4810K is closely related MMD risk in China and has given rise to an earlier onset age and more severe PCA involvement.